Actor–Partner Interdependence Model Analysis of Sexual Communication and Relationship/Family Planning Factors Among Immigrant Latino Couples in the United States. Issue 5 (4th May 2017) - Matsuda, Yui
ABSTRACT: The Latino population in the United States is quickly growing, and its unintended pregnancy rate is increasing. To decrease unintended pregnancies, couples must mutually agree on family planning. Communication between partners is one key factor identified in successful family planning for couples. Therefore, the purpose of this study was to examine sexual communication and its associations with sexual relationship power, general communication, and views on family planning. The Actor–Partner Interdependence Model was used to analyze dyadic influences of the chosen variables. Forty immigrant Latino couples were recruited from prenatal care clinics. The study results were grouped according to the three types of power structures: exhibition of men's traditional machismo values, exhibition of women's increased power in their relationships, and exhibition of men's and women's own empowerment with sexual communication. There was a negative association between men's views on family planning and women's sexual communication (exhibition of machismo values); a negative association between women's sexual relationship power and their partners' sexual communication (exhibition of women's increased power); and positive associations between men's and women's general communication and sexual communication (exhibition of men's and women's own empowerment). Dyadic influences of sexual communication and associated variables need to be incorporated into interventions to facilitate family planning for couples.